2003
DOI: 10.22358/jafs/67757/2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented products on performance, faecal pH, <i>Enterobacteriaceae</i> and lactic acid bacteria counts and interrelationships, and plasma cholesterol concentration in rats

Abstract: Fermented products (FP), a mixed product of raw fish, sea weed, rice bran, sugar cane juice, were obtained in a process of fermentation using combination of cultures of lactic acid bacteria (LAB). The objectives of this study were to assess the effects of diets with different levels of FP on performance, faecal pH, Enterobacteriaceae and LAB counts and their relationships, and plasma cholesterol concentration in rats. A total of 24 Sprague Dawley (10 weeks of age) female rats were assigned individually into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
5
13
1
Order By: Relevance
“…The addition of SDM to the diets of rats significantly decreased the Enterobacteriaceae counts in the faeces in the third week of the experiment. The results showed similar trends to those reported in pigs (Urlings et al, 1993) and rats (Loh et al, 2003). The reduced shedding of Enterobacteriaceae in the faeces was also found in studies using fermented feed containing Lactobacillus cultures (Mikkelsen and Jensen, 1998;Loh et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The addition of SDM to the diets of rats significantly decreased the Enterobacteriaceae counts in the faeces in the third week of the experiment. The results showed similar trends to those reported in pigs (Urlings et al, 1993) and rats (Loh et al, 2003). The reduced shedding of Enterobacteriaceae in the faeces was also found in studies using fermented feed containing Lactobacillus cultures (Mikkelsen and Jensen, 1998;Loh et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…The results showed similar trends to those reported in pigs (Urlings et al, 1993) and rats (Loh et al, 2003). The reduced shedding of Enterobacteriaceae in the faeces was also found in studies using fermented feed containing Lactobacillus cultures (Mikkelsen and Jensen, 1998;Loh et al, 2003). Similarly, probiotics supplemented to piglets within a day of birth significantly reduced the numbers of Salmonella choleraesuis (Fedorka et al, 1999) and E. coli detected in gut tissues and faeces.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The FP used in this study was rich in LAB, a low pH and high concentration of lactic acid (Loh et al, 2003b). It has been shown that LAB has antagonistic effect on harmful bacteria either in vitro or in vivo studies (Lindgren and Dobrogosz, 1990;Forestier et al, 2001;Foo et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the total cholesterol and triglyceride levels were lower than in pigs that were fed the CON diet. In previous studies, Loh et al (2003) showed a decrease in plasma cholesterol levels in the fermented product group compared with the nonfermented product group in rats. Chu et al (2011) reported that fermented diets could have an effect on reducing HDL and LDL cholesterol in fattening pigs.…”
Section: Discussionmentioning
confidence: 77%